The C242T polymorphism of the p22-phox gene (CYBA) is associated with higher left ventricular mass in Brazilian hypertensive patients - Krieger José E; Vercesi Aníbal E; Mill José G; Matos-Souza José R; Cipolli José A; Pio-Magalhães José A; Ronchi Juliana A; Ferreira-Sae Maria C; Schreiber Roberto; Franchini Kleber G; Pereira Alexandre C; Nadruz Junior Wilson (BMC, 2011)
Abstract Background Reactive oxygen species have been implicated in the physiopathogenesis of hypertensive end-organ damage. This study investigated the impact of the C242T polymorphism of the p22-phox gene (CYBA) on left ventricular structure in Brazilian hypertensive subjects. Methods We cross-sectionally evaluated 561 patients from 2 independent centers [Campinas (n = 441) and Vitória (n = 120)] by clinical history, physical examination, anthropometry, analysis of metabolic and echocardiography parameters as well as p22-phox C242T polymorphism genotyping. In addition, NADPH-oxidase activity was quantified in peripheral mononuclear cells from a subgroup of Campinas sample. Results Genotype frequencies in both samples were consistent with the Hardy- Weinberg equilibrium. Subjects with the T allele presented higher left ventricular mass/height2.7 than those carrying the CC genotype in Campinas (76.8 ± 1.6 vs 70.9 ± 1.4 g/m2.7; p = 0.009), and in Vitória (45.6 ± 1.9 vs 39.9 ± 1.4 g/m2.7; p = 0.023) samples. These results were confirmed by stepwise regression analyses adjusted for age, gender, blood pressure, metabolic variables and use of anti-hypertensive medications. In addition, increased NADPH-oxidase activity was detected in peripheral mononuclear cells from T allele carriers compared with CC genotype carriers (p = 0.03). Conclusions The T allele of the p22-phox C242T polymorphism is associated with higher left ventricular mass/height2.7 and increased NADPH-oxidase activity in Brazilian hypertensive patients. These data suggest that genetic variation within NADPH-oxidase components may modulate left ventricular remodeling in subjects with systemic hypertension.